Hippocampal contributions to serial‐order memory. Issue 3 (5th November 2018) - Long, Nicole M.; Kahana, Michael J.
Abstract: Our memories form a record not only of our experiences, but also of their temporal structure. Although memory for the temporal structure of experience likely relies on multiple neural systems, numerous studies have implicated the hippocampus in the encoding and retrieval of temporal information. This review evaluates the literature on hippocampal contributions to human serial‐order memory from the perspective of three cognitive theories: associative chaining theory, positional‐coding theory and retrieved‐context theory. Evaluating neural findings through the lens of cognitive theories enables us to draw more incisive conclusions about the relations between brain and behavior.